P237 Superior predictive value of intestinal ultrasound over endoscopic severity for colectomy risk in patients with ulcerative colitis. (30th January 2023) - Piazza, N; Noviello, D; Filippi, E; Conforti, F; Furfaro, F; Fraquelli, M; Fiorino, G; Danese, S; Allocca, M; Caprioli, F
Abstract: Background: Up to 15% of patients with ulcerative colitis (UC) do not respond to medical therapies and ultimately require colectomy for disease control. Baseline endoscopic severity and failure to achieve endoscopic healing, as defined by a Mayo Endoscopic Subscore (MES) ≤ 1, following therapy have been associated with an increased risk of colectomy. Intestinal ultrasound severity, as defined by a Milan ultrasound criteria (MUC) score > 6.2, has been associated with an increased risk of colectomy. The aim of this study is to evaluate and compare MES and MUC in predicting the need for colectomy in patients with UC. Methods: This is a double-center prospective observational cohort study. All consecutive adult UC patients between January 2016 and January 2020 requiring colonoscopy received intestinal ultrasound within 20 ± 12 days in a blinded fashion. Colectomies were evaluated during the follow-up. Univariable and multivariable Cox regression analyses were used to identify variables independently associated with colectomy risk. ROC analysis was used to compare baseline MES and MUC scores' performances in predicting colectomy. Results: A total of 141 patients were enrolled (Table 1). Overall 13 patients underwent colectomy during 256.41 person-years of observation time. At baseline, patients requiring colectomy had increased mean values of MUC as compared to patients not undergoing surgery (6.84 ± 2.49 vs 10 ± 1.9, p <0.001). At univariate analysis, MES (HR: 3.15, 95% CI:1.18 – 8.37, p = 0.02) and MUC (HR: 1.48, 95% CI:1.19 – 1.76, p <0.001) were associated with colectomy risk. At multivariable analysis, MUC but not MES was associated with colectomy risk (HR: 1.46, 95% CI: 1.06 – 2.02, p 0.02). As compared with MES, MUC score demonstrated a higher AUROC (0.83, 95% CI: 0.75 – 0.92 vs 0.71 95% CI: 0.62 – 0.80) and better performance for assessing the need for colectomy ( p = 0.02) (Figure 1). The optimal MUC score cutoff for predicting colectomy, as assessed by the Youden index, was 7.72, with a sensitivity and specificity of 1 and 0.6, respectively. Conclusion: Ultrasound severity, as assessed by the MUC score, is superior to endoscopic severity in predicting the need for colectomy in patients with UC. A baseline MUC score of < 7.72 may rule out colectomy risk in UC patients.